Eugenol como anestésico para jundiá (Rhamdia voulezi) em diferentes pesos - Diemer, Odair [UNESP]; Neu, Dacley Hertes; Bittencourt, Fabio [UNESP]; Signor, Altevir; Boscolo, Wilson Rogerio; Feiden, Aldi (Universidade Estadual de Londrina (UEL), 2012)
The study aimed to find the better concentration of eugenol for anesthesia of silver catfish (Rhamdia voulezi) with different weights. Were used 240 catfish distributed in randomized blocks in factorial scheme (5x4) total 20 treatments, in others words, five different weights: 32,5; 75; 150; 300 e 450g and four eugenol concentrations: 50, 75, 100 e 125 mg.l(-1). For each treatment were used 12 fish randomly chosen and exposed individually for each concentration. After of anesthesia the fish were transferred for net-cage with 0,7m(3), being fed and observed by 96 hours for monitoring of mortality. The eugenol was efficient for anesthesia in silver catfish all concentrations and weights and after of 96 hours no mortality have been verified. At these experimental conditions the best concentration of eugenol for anesthetic inducing and recuperation of silver catfish with weight varying from 32,5 and 450 g is 50 mg.l(-1).
Eugenol as anesthetic for silver catfish (Rhamdia voulezi) with different weight
Keywords: Aquaculture; clove oil; fish management